Staphylococcus epidermis e Staphylococcus haemolycus: detecção de genes de biofilme, toxinas, resistência a antimicrobianos e tipagem clonal em isolados de hemoculturas - Pinheiro, Luiza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Staphylococcus epidermidis and Staphylococcus haemolyticus are opportunistic pathogens that cause infections which are mainly related to the formation of a biofilm. Enterotoxins, superantigens related to food poisoning and hemolysins, molecules able to lyse mammalian cells, seem to be involved in the pathogenesis of staphylococcal infections, although the question remains whether they represent important virulence factors in these organisms. The indiscriminate use of antimicrobial drugs has selected strains that are resistant to oxacillin, in addition to isolates with reduced vancomycin susceptibility. Oxacillin resistance is encoded by the mecA gene which is carried on a mobile genetic element, SCCmec. New antimicrobial drugs such as linezolid, tigecycline, daptomycin and quinupristin/dalfopristin are being used for the treatment of infections caused by multidrug-resistant staphylococci. The objective of this study was to characterize S. epidermidis and S. haemolyticus strains isolated from blood cultures regarding the presence of hemolysin and enterotoxin genes, antimicrobial susceptibility, and clonal profile. Investigation of the mecA gene by real-time PCR in 169 isolates revealed the presence of the gene in 100% of S. haemolyticus isolates and 92.9% of S. epidermidis. The most frequent SCCmec types determined by multiplex PCR were types I and III, respectively. The minimum inhibitory concentrations (MICs) of linezolid, tigecycline, daptomycin, quinupristin/dalfopristin and vancomycin determined by the Etest® showed that 4.7% of the isolates were resistant to tigecycline and 1.2% were resistant or intermediate resistant to quinupristin/dalfopristin. The maximum MIC for vancomycin was 3 μg/ml. Broth microdilution revealed vancomycin MICs of 0.25 to 2 μg/ml, showing 88.2% agreement with the Etest results. Pulsed-field gel electrophoresis (PFGE) typing revealed the presence of S. epidermidis ...

Staphylococcus epidermidis e Staphylococcus haemolyticus são considerados patógenos oportunistas, cujas infecções estão principalmente associadas à produção de biofilme. As enterotoxinas, superantígenos relacionados a intoxicações alimentares, e as hemolisinas, moléculas capazes de causar lise de membranas celulares, parecem estar associadas à patogênese das infecções estafilocócicas, apesar de ainda ser questionado se elas constituem fatores de virulência importantes nesses organismos. O uso indiscriminado de antimicrobianos vem selecionando cepas resistentes à oxacilina com menor suscetibilidade à vancomicina. A resistência à oxacilina é codificada pelo gene mecA, contido em um elemento genético móvel, denominado SCCmec. Novos antimicrobianos, como a linezolida, tigeciclina, daptomicina e quinupristina/dalfopristina vêm sendo empregados no tratamento de infecções por estafilococos multirresistentes. Este estudo objetivou caracterizar S. epidermidis e S. haemolyticus isolados de hemoculturas quanto à presença de genes de hemolisinas, enterotoxinas, suscetibilidade aos antimicrobianos e perfil clonal. Cento e sessenta e nove isolados foram pesquisados quanto à presença do gene mecA por PCR em tempo real, estando presente em 100% dos S. haemolyticus e 92,9% dos S. epidermidis, cujos tipos de SCCmec mais frequentes, determinados por PCR Multiplex, foram, respectivamente, I e III. Os MICs (Concentração Inibitória Mínima) de linezolida, tigeciclina, daptomicina, quinupristina/dalfopristina e vancomicina foram obtidos por Etest® e revelaram 4,7% de isolados resistentes à tigeciclina, 1,2% resistentes ou com resistência intermediária à quinupristina/dalfopristina, sendo o MIC máximo de vancomicina igual a 3 μg/ml. A microdiluição em caldo para vancomicina mostrou MICs de 0,25 a 2 μg/ml, concordando em 88,2% com os resultados obtidos com Etest®. A tipagem por PFGE...
Keywords: Estafilococos; Biofilme; Toxinas; Infecções estafilococicas; Biofilms